PEDAGOGICAL CONCEPT OF TEACHING CHILDREN WITH HEARING DISABILITIES TO READ SPECIAL FEATURES - Toshpulova Nodira (Bright Mind Publishing, 2025)
This article presents a pedagogical concept for teaching children with hearing impairments to read. The main aspects of its specific features and the application of didactic principles in native language lessons for children with hearing impairments are discussed in the general pedagogy of modern secondary schools.
Keywords: Scientificity, awareness and activity, clarity, demonstrativeness, thoroughness, individual approach, consistency and regularity.